(untitled) (Marketing Journal, 2025)
The article explores the essence of motivational approaches. It analyzes the motivational methods used in the marketing activities of sewing and knitwear enterprises. The study also provides recommendations for the application of motivational approaches in the marketing practices of textile and knitwear companies.